How attention and knowledge modulate memory: The differential impact of cognitive conflicts on subsequent memory—A review of a decade of research - Muhmenthaler, Michèle C.; Dubravac, Mirela; Meier, Beat (Frontiers in Cognition, 2023)
In order to cope with cognitive conflicts, attention and knowledge are required. In some conditions, cognitive conflicts can boost subsequent memory and in other conditions, they can attenuate subsequent memory. The goal of the present study is to provide a narrative review of studies from the last decade in which Stroop or flanker conflicts, task switching, perceptual disfluency or semantic incongruence were manipulated at study. We propose an integrative framework considering attentional mechanisms and knowledge structures. Attentional mechanisms can refer to conflict resolution, which is required to explain the memory benefit for incongruent stimuli in Stroop and Flanker paradigms. Attentional mechanisms can also refer to attention allocation, which is required to explain the memory cost for targets and the memory benefit for task-irrelevant distractors in task-switching paradigms. Moreover, attention allocation policies can also account for the inconsistent results for perceptual disfluency manipulations. Prior knowledge is required to explain effects of semantic congruency and incongruency: Information that is expected, or congruent with prior knowledge, is better remembered, namely by pre-existing schemata. Moreover, information that is unexpected or incongruent with prior knowledge attracts attention and is better remembered. The impact of prior knowledge on memory performance thus results in a U-shape function. We integrate the findings according to this framework and suggest directions for future research.